Penerapan Metode Moora Dalam Menentukan Parfume Terbaik Berdasarkan Kepribadian - Halimatusakdiah Pohan; Dwita Elisa Sinaga (LPPM STIKOM Tunas Bangsa, 2020)
Parfume is one of the distinctive scented liquids that people use to eliminate body odor, in the use of parfume, people tend to have different types of parfume according to their personality type. Based on many personalities that exist in society, the writer uses one personality Sangunis where someone who has this personality is cheerful, friendly, warm and friendly but prefers a pungent aroma because usually someone with a Sangunins personality likes to socialize wherever they are. In this article the author uses one of the SPK methods MOORA, which has the advantage of being simple, stable and easy to implement, so it is hoped that the Moora method can help someone in making a perfume selection decision.